2021
DOI: 10.1002/ps.6705
|View full text |Cite
|
Sign up to set email alerts
|

Helicoverpa armigera and Helicoverpa zea hybridization: constraints, heterosis, and implications for pest management

Abstract: BACKGROUND: The invasion of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) into the New World has made it possible for this pest to hybridize with a native American species, H. zea (Boddie), under natural conditions. We investigated the viability and development of hybrids of these two Helicoverpa species. We reared the parental species and evaluated crosses between H. armigera males and H. zea females and vice versa, two intercrosses between hybrids, and eight backcrosses between hybrids and parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 106 publications
0
15
0
3
Order By: Relevance
“…The relevance of analysis to detect hybridization between H. zea and H. armigera is due to the probability of new formations of adaptive genes ( 44 , 47 ), which can have an impact on ecological attributes of the hybrids, such as a wider host range ( 48 , 49 ) and performance of management tools ( 28 , 50 , 51 ). However, a study documenting biological parameters of hybrids between H. armigera and H. zea , under laboratory conditions, indicated that egg viability is a critical factor for the success of the hybridization, with overall egg viability of 14% ( 52 ), when compared with more than 85% egg viability in the parental species. The authors concluded that there are reproductive limitations for hybridization, including barriers from the lock-and-key mechanisms presented in the noctuid genitalia morphology ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of analysis to detect hybridization between H. zea and H. armigera is due to the probability of new formations of adaptive genes ( 44 , 47 ), which can have an impact on ecological attributes of the hybrids, such as a wider host range ( 48 , 49 ) and performance of management tools ( 28 , 50 , 51 ). However, a study documenting biological parameters of hybrids between H. armigera and H. zea , under laboratory conditions, indicated that egg viability is a critical factor for the success of the hybridization, with overall egg viability of 14% ( 52 ), when compared with more than 85% egg viability in the parental species. The authors concluded that there are reproductive limitations for hybridization, including barriers from the lock-and-key mechanisms presented in the noctuid genitalia morphology ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…High migratory capacity, the ability to feed on a wide range of shared host plants, and rapidly developed resistance to all of the commonly used groups of insecticide chemistry (Fitt 1989 ; McCaffery 1998 ; Feng et al 2005 ) have facilitated its global spread and impact. H. armigera has recently extended its range into South America which, coupled with its potential to also reach North America (Czepak et al 2013 ; Tay et al 2013 ; Kriticos et al 2015 ), poses a serious problem for invasive pest management (Cordeiro et al 2020 ; Rios et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current Brazilian crop production systems, outbreaks of Helicoverpa species are favored by the overlapping and simultaneous cultivation of host plants, including soybean, maize, cotton, tomatoes, and dry bean crops [4]. Studies also reported the occurrence of interspecific hybridization between H. armigera and H. zea under laboratory conditions [5][6][7]. The successful hybridization in a restricted environment suggests that potential for multiple mating events in the field may provide opportunities to select well-adapted hybrid phenotypes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies also reported the occurrence of interspecific hybridization between H. armigera and H. zea under laboratory conditions [5][6][7]. The successful hybridization in a restricted environment suggests that potential for multiple mating events in the field may provide opportunities to select well-adapted hybrid phenotypes [7]. Cases of resistance to Bt proteins in H. zea have been reported in the U.S. and China [8][9][10][11] and decreases in susceptibility to Cry proteins by H. armigera have been reported in U.S., India, and China [12,13].…”
Section: Introductionmentioning
confidence: 99%